(untitled) (Research, Society and Development, 2024)
Around the world, people with disabilities are less likely to be employed or receive adequate assistance and education for employment than the general population. Furthermore, important social functions are performed for people with disabilities, including recognition as full members of society, earning income, establishing contacts with others, contributing to society, and structuring time. The objective of this article is to address People with Disabilities - PCDS in the job market taking, into consideration the essentiality of social inclusion in companies. To implement this, bibliographical research was carried out. Disability inclusion allows everyone to have equal rights in society – including in the workplace. Having a job or a professional career is a normal part of many people’s lives, but there can be barriers that make it difficult for a person with a disability to find and keep a job. Adopting an inclusive stance can increase opportunities in the workplace. It is concluded that the national legislation is far from reality, as society does not respect the space protected for PWDs. Therefore, it is not enough to create laws so that people with disabilities can enter the job market, they must be respected, that is, complied with, in addition to respecting their rights.